Censorship detected in HN (Honduras) - Voidly (2026)
CRITICAL severity censorship detected in Honduras. Confidence: 70%. Data sourced from OONI.
Censorship Incident ID: HN-2026-0055
Keywords: censorship; HN; censorship; critical